Pengaruh Budaya Populer Terhadap Pola Pikir Remaja di Indonesia - Ahmad Faqih; Ilah Holilah (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the influence of popular culture on the mindset of adolescents in Indonesia. Popular culture, such as music, films, social media, and fashion trends, has a significant role in shaping the way today's adolescents think, behave, and act. Using a descriptive qualitative method, data was collected through literature studies, observations, and interviews with several adolescents from various backgrounds. The results of the study indicate that popular culture can influence adolescents' perceptions of self-identity, social values, and lifestyle. In addition, the flow of globalization also strengthens the influence of foreign culture, causing a shift in the mindset of adolescents who tend to be more individualistic and consumptive. However, popular culture also provides space for creative expression and forms solidarity between adolescents. Therefore, it is important for educators and parents to provide assistance and media literacy so that adolescents are able to filter information critically and still uphold local values. This study is expected to be a reference in understanding the psychosocial dynamics of adolescents in the digital era.